ANALYZING THE USE OF GOOGLE TRANSLATE AMONG STUDENTS AND STUDENTS (SMA) - Irenza Prahdiah; Rifqi Rizqullah; Ivan Achmad Nurcholis (Jurnal Review Pendidikan dan Pengajaran (JRPP), 2023)
The use of Google Translate in English lessons for high school students has become a research topic that has attracted the attention of many scholars. This study analyzes the use of this service as an English learning medium in Package B. The purpose of this study is to explore the advantages and disadvantages of using this service. The results show that using the service can help students learn vocabulary comprehension, sentence structure, and word spelling pronunciation. The students can use the service to help them learn vocabulary in nonnative languages. It is known that the benefits that boarding learners experience when using the services relate to how quickly they can find the meaning of the word they want to translate.